Is Panama really your tax haven? Secrecy jurisdictions and the countries they harm - Petr Jansky; Markus Meinzer; Miroslav Palansky (Charles University in Prague, Institute of Economic Studies (IES), 2018)
Secrecy jurisdictions provide services that enable the residents of other countries to escape the laws and regulations of their home economies, evade tax, or hide their legally or illegally obtained assets. Recent offshore leaks offer only a limited and biased view of the world of financial secrecy. In this paper we quantify which secrecy jurisdictions provide secrecy to which countries and assess how successful countries are in targeting these jurisdictions with their policies. To that objective we develop the Bilateral Financial Secrecy Index (BFSI) and estimate it for 86 countries by quantifying the financial secrecy supplied to them by up to 100 secrecy jurisdictions. We then evaluate two major recent policy efforts by comparing them with the results of the BFSI. First, we focus on the blacklisting process of the European Commission and find that most of the important secrecy jurisdictions for EU member states have been identified by the lists. Second, we link the results to data on active bilateral automatic information exchange treaties to assess how wellaimed are the policymakers' limited resources. We argue that while low-secrecy jurisdictions' gains are maximized if a large share of received secrecy is covered by automatic information exchange, tax havens aim not to activate these relationships with countries to which they supply secrecy. Our results show that so far, some major secrecy jurisdictions successfully keep their most prominent relationships uncovered by automatic information exchange, and activating these relationships may thus be an effective tool to curb secrecy.
Keywords: F36; F63; F65; H26; O16; 330; tax havens; secrecy jurisdictions; financial secrecy; financial transparency; offshore finance; automatic exchange of information; global development